CuAAC-inspired synthesis of 1,2,3-triazole-bridged porphyrin conjugates: an overview - Singh, Dileep Kumar (Beilstein Journal of Organic Chemistry, 2023)
Among all the available approaches in organic synthesis, the “click chemistry” protocol is very common nowadays to covalently connect two diverse moieties in a single framework. Therefore, this review focuses on the synthesis and photophysical studies of β- and meso-substituted and 1,2,3-triazole-fused porphyrin conjugates. All of the porphyrin conjugates discussed here are synthesized via a copper(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction between an azide and a terminal alkyne, also popular as "click reaction" or CuAAC reaction. Moreover, the 1,2,3-triazole ring also serves as a spacer and an electron transfer bridge between the porphyrin and the attached chromophores. In order to provide a critical overview of the synthesis and properties of various porphyrin-triazole hybrids, this review will discuss some of the key reactions involved in the preparation of triazole-linked porphyrin conjugates.
Keywords: azide–alkyne; click chemistry; CuAAC; 1,3-dipolar cycloaddition; porphyrin; 1,2,3-triazole